2005
DOI: 10.1373/clinchem.2005.056374
|View full text |Cite
|
Sign up to set email alerts
|

Biological Variation of Vitamins in Blood of Healthy Individuals

Abstract: Background: Components of biological variation can be used to define objective quality specifications (imprecision, bias, and total error), to assess the usefulness of reference values [index of individuality (II)], and to evaluate significance of changes in serial results from an individual [reference change value (RCV)]. However, biological variation data on vitamins in blood are limited. The aims of the present study were to determine the intra-and interindividual biological variation of vitamins A, E, B 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 28 publications
7
27
0
Order By: Relevance
“…Free plasma amino acids exhibit relatively low CV I values, similar to those reported for other diet related metabolites such as, plasma vitamins (29). The essential amino acids showed lower CV I than non-essential amino acids.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Free plasma amino acids exhibit relatively low CV I values, similar to those reported for other diet related metabolites such as, plasma vitamins (29). The essential amino acids showed lower CV I than non-essential amino acids.…”
Section: Discussionsupporting
confidence: 75%
“…The RCVs were high for amino acids primarily due to their within-subject component of variation, a common finding in other diet-related metabolites studied in plasma (29). Therefore, relatively large differences between results of sequential samples would be required, i.e., a difference of 31% between two consecutive results in hyperphenylalaninemia monitoring would be necessary to indicate significant changes as a result of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier research has reported intra-and interindividual variations in serum carotenoid concentrations in small samples (Tangney et al, 1987;Yong et al, 1994;Talwar et al, 2005), in smokers (Block et al, 2006) and in one large sample of the European Prospective Investigation of Cancer (EPIC) . Yet large-scale multicenter trials, such as the Polyp Prevention Trial (PPT; Appendix), or observational research like the EPIC, contribute additional sources of variation in serum carotenoid concentrations due to potential within-and between-center and seasonal differences in serum levels .…”
Section: Introductionmentioning
confidence: 99%
“…The limit of detection of our assay is 0.08 nmol/L, which is comparable to that reported by others (19 -22, 24, 33 ). The between-run imprecision of the assay is well below the reported desirable imprecision goal (CV 19%) based on biological variation of phylloquinone (36 ).…”
Section: 33 )mentioning
confidence: 77%